2017
DOI: 10.1039/c7ra01352c
|View full text |Cite
|
Sign up to set email alerts
|

Review on the mass transfer performance of CO2 absorption by amine-based solvents in low- and high-pressure absorption packed columns

Abstract: An overview on the experimental works for obtaining KGCO2aV for low- and high-pressure absorption packed columns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(42 citation statements)
references
References 89 publications
1
41
0
Order By: Relevance
“…On the other hand, Zivdar et al [24] reported pressure drop values from 15 to 83 mm of water per meter of gauze-type-structured packing in an air-water column. In addition, Afkhamipour and Mofarahi [25] carried out a deep review of the operation conditions of different low-pressure absorption columns and did not consider the pressure drop as a paramount operation parameter.…”
Section: Packed-column Performance As a Function Of Operation Parametersmentioning
confidence: 99%
“…On the other hand, Zivdar et al [24] reported pressure drop values from 15 to 83 mm of water per meter of gauze-type-structured packing in an air-water column. In addition, Afkhamipour and Mofarahi [25] carried out a deep review of the operation conditions of different low-pressure absorption columns and did not consider the pressure drop as a paramount operation parameter.…”
Section: Packed-column Performance As a Function Of Operation Parametersmentioning
confidence: 99%
“…The kinetic network modelling CO 2 in aqueous alkanolamine solutions requires accurate diffusion coefficients of all solvent components present in solution. [19][20][21] Experimental viscosity studies of individual constituents do not allow an extrapolation of diffusion coefficients to the reactive solution. Therefore, structurebased simulations are indispensable to provide these missing data and only classical MD simulations allow a sufficient sampling and averaging over long trajectories and a large number of particles to give accurate results.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in an aero‐engine bearing chamber, the use of oil film on the internal surface plays an essential role in removing heat from the chamber, where the surface of oil film is strongly affected by the shearing airflow associated with the high‐speed rotating parts within the chamber . Furthermore, in the amine process, the packed column (random or structured) are widely used in industry to separate CO 2 from fossil fuels, which in fact are important source of energy production in the world . In this absorption process, CO 2 is removed from the gas phase to the liquid phase by using an amine base solvent within a packed contactor.…”
Section: Introductionmentioning
confidence: 99%
“…26 Furthermore, in the amine process, the packed column (random or structured) are widely used in industry to separate CO 2 from fossil fuels, which in fact are important source of energy production in the world. 27,28 In this absorption process, CO 2 is removed from the gas phase to the liquid phase by using an amine base solvent within a packed contactor. In this application, the development of surface wave at the gas-liquid interface plays a major role in the mass transfer of CO 2 from the gas phase, and therefore, its controlling process is of practical interest.…”
mentioning
confidence: 99%